2014
DOI: 10.3109/09546634.2013.873763
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the adjuvant effect of tacrolimus in the management of pemphigus vulgaris: A randomized controlled trial

Abstract: Tacrolimus effects are comparable to azathioprine as pemphigus vulgaris adjuvant treatment, also it has less severe side effects. Trial registration No. IRCT2012073010450N1 available at www.IRCT.ir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…In the sole trial comparing tacrolimus and azathioprine, no benefit was noted in CR rate, cumulative glucocorticoid dose, time to achieve disease control, rate of withdrawal due to adverse events, or rate of death [20].…”
Section: Tacrolimusmentioning
confidence: 94%
See 2 more Smart Citations
“…In the sole trial comparing tacrolimus and azathioprine, no benefit was noted in CR rate, cumulative glucocorticoid dose, time to achieve disease control, rate of withdrawal due to adverse events, or rate of death [20].…”
Section: Tacrolimusmentioning
confidence: 94%
“…The follow-up period ranged from 1 to 60 months. The characteristics and main efficacy results of the 20 trials are displayed in Table 1 [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The majority of studies included patients with newly diagnosed disease [8, 10-12, 14, 16, 18, 21] or a combination of newly diagnosed disease and recurrent disease [9,13,19,20,22,25,27].…”
Section: Trials Included In the Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Several initiatives recently enacted by the Australian government, as well as cheaper generic availability of pharmaceuticals after patent expiry, have introduced cost-savings measures and these introduce uncertainty about future pricing structures and PBS expenditures. However, by considering the increasing number of kidney transplant operations, functioning kidney transplants in the community and potential for widening of the subsidized indications, particularly for mycophenolate [47][48][49], tacrolimus [50] and everolimus [51][52][53], immunosuppressant expenditure will continue to rise into the future. It is not likely that generic formulations …”
Section: Discussionmentioning
confidence: 99%
“…There are also two case reports on the successful use of systemic tacrolimus for recalcitrant PV unresponsive to prednisolone, azathioprine (AZA), mycophenolate mofetil (MMF), dapsone, and cyclophosphamide (CP) [6]. A randomized controlled trial demonstrated that tacrolimus effects are comparable to AZA as PV adjuvant treatment, although with less severe side effects [7]. Takae et al used a pemphigus mouse model to evaluate various immunosuppressive therapies and reported the suppressive effect of tacrolimus on the production of anti-Dsg3 IgG [8].…”
Section: Introductionmentioning
confidence: 99%